Electron-capture decays mimicking axionic transitions - Agnihotri, Aagrah (2024)
For the first time, estimates for β decay rates are made that are necessary for experimental searches of low-mass axions. Low-mass axions are potential dark matter candidates, hence, searches of low-mass axions have implications beyond standard model physics. For terrestrial searches of low-mass axions, 44Ti, 57Co, and 139Ce are popular sources. The sources decay purely via electron-capture and populate M1-decaying excited states in daughter nuclei. These M1-decaying nuclear-excited states are also expected to decay via axion production. The GS-to-GS branches of the electron-capture decays of 44Ti, 57Co, and 139Ce, not yet measured are expected to have identical experimental signatures as the axionic transitions. These GS-to-GS transitions are rare, and experiments call for theory predictions for transition rates of these decay branches. The scope of the work done addresses such needs of the experiments.